Why Are More Sovereigns Issuing in Euros? : Choosing between USD and EUR-Denominated Bonds - Velandia, Antonio; Cabral, Rodrigo (World Bank, Washington, DC, 2018)
This paper presents and discusses the arguments offered by several sovereigns that have joined a trend starting in 2013 whereby sovereign and corporate issuers, especially in Latin America, have gradually replaced a portion of the funding raised in U.S. dollars with euros. The trend seems to respond to the divergent monetary policies followed by the U.S. Federal Reserve Board and the European Central Bank. The selected country cases state strategic and tactical arguments for increasing their issuance in euros. The strategic reasons relate to internal currency benchmarks and their rationale. In some cases, such substitution is supported by the argument that further diversification in the investor base was needed. This argument was reinforced by the relatively tight conditions in the U.S. dollar market. Tactical arguments refer to the need to open the market to the private sector and raise funding in euros, or the need to access new investors as a preliminary step to attract them to the domestic market. Several countries also admit that the optical effect of lower coupons was a relevant consideration. This paper highlights that it is important that sovereigns avoid making decisions by comparing nominal coupons in both currencies. More important, a formal debt management strategy, including a target for the currency composition, should guide debt managers. Without a strategy, the debt manager cannot tell how the issuance in a particular currency affects the exposure of the debt portfolio to foreign currency risk and helps or not in achieving the debt management objectives.